Analisis Hukum Ekonomi Syariah Terhadap Praktik Diskon Tiket Bioskop Murah: Tinjauan Maslahah, Mudharabah dan Implikasi Bagi Konsumen dan Produsen - Lalah Sibgah; Resha Atkya Aulia; Jaenudin J; Dian Herdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The practice of offering cinema ticket discounts has become a common marketing strategy in Indonesia’s entertainment industry, particularly through digital platforms and membership programs. This study examines cinema ticket discount practices from the perspective of Islamic economic law, focusing on the concepts of maslahah (public benefit), mudharabah (profit-sharing), and their implications for consumers and producers. Using a descriptive-analytical qualitative approach, the study analyzes discount mechanisms, pricing structures, and their impact on stakeholders through the lens of Islamic legal principles. The findings indicate that offering cinema ticket discounts can be justified in Islamic law when they fulfill the criteria of maslahah by providing accessibility to entertainment, supporting economic circulation, and ensuring fairness in transactions. However, certain practices, such as extreme price manipulation, misleading marketing, and exploitation of consumer behavior, raise concerns regarding gharar (uncertainty) and dharar (harm). The mudharabah framework provides insights into the profit-sharing dynamics between cinemas, distributors, and digital platforms, emphasizing the need for transparent and fair partnerships. This study recommends that discount practices be regulated to ensure compliance with Islamic principles of fairness, transparency, and shared benefit, while maintaining industry sustainability and consumer protection.